2023
DOI: 10.1097/md.0000000000032796
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical activity and diabetes in middle-aged and elderly people

Abstract: To investigate the association between diabetes symptoms and physical activity (PA) levels among middle-aged and older Chinese adults. Data for this study were obtained from 2018 Charles data. Z test, logistic regression analysis, and linear hierarchical regression analysis were performed in 5352 individuals aged ≥50 years with complete information. In terms of diabetes, 6.8% of the middle-aged and elderly people with diabetes were detected, and 93.2% of the middle-aged and elderly peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Additionally, a recent Chinese study examined the relationship between level of physical activity and diabetes symptoms among old people. The results showed a significant link between physical inactivity and diabetes in this population (Tian et al, 2023). It is important to note that physical activity can prevent and treat diabetes in old people.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Additionally, a recent Chinese study examined the relationship between level of physical activity and diabetes symptoms among old people. The results showed a significant link between physical inactivity and diabetes in this population (Tian et al, 2023). It is important to note that physical activity can prevent and treat diabetes in old people.…”
Section: Discussionmentioning
confidence: 59%
“…It is important to note that physical activity can prevent and treat diabetes in old people. Therefore, it is crucial for individuals to increase their physical activity to improve their overall health and reduce their risk of chronic illnesses (Tian et al, 2023). This suggests that persons in their forties and fifties should prioritize increasing their physical activity to decrease their risk of developing diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Physical inactivity is associated with insulin resistance via several molecular mechanisms, including beta cells' insufficiency and inflammation 36 . A previous study showed that high physical activity was associated with a low risk of diabetes mellitus in middle‐aged and older adults 37 . Additionally, psychological changes, social changes, and multiple medications can be mentioned as other examples.…”
Section: Discussionmentioning
confidence: 99%
“… 36 A previous study showed that high physical activity was associated with a low risk of diabetes mellitus in middle‐aged and older adults. 37 Additionally, psychological changes, social changes, and multiple medications can be mentioned as other examples. One of the psychological changes with age is increasing depression symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The key role of regular physical activity in the management of T2D, reducing chronic consequences and improving quality of life has been proven [3,4]. Despite the vital role of physical activity in controlling the complications of T2D, estimates indicate that 37-60% of T2D patients do not exercise, and this low amount worsens with age [5].…”
Section: Introductionmentioning
confidence: 99%